Pan American League of Associations for Rheumatology Recommendations for the Treatment of Psoriatic Arthritis - Daniel G. Fernández‐Ávila; Wilson Bautista‐Molano; María Lorena Brance; G. Ávila; Rubén Burgos‐Vargas; José Francisco Díaz Coto; L. Gutiérrez; Marwin Gutiérrez; Enrique Giraldo Ho; Sebastián Ibañez; Edwin Jáuregui; Vanessa Ocampo; et al. (2024)
Objective Psoriatic arthritis (PsA) is chronic disease that compromises multiple domains and might be associated with progressive joint damage, increased mortality, functional limitation, and considerably impaired quality of life. Our objective was to generate evidence-based recommendations on the management of PsA in Pan American League of Associations for Rheumatology (PANLAR) countries. Methods We used the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE)-ADOLOPMENT approach to adapt the 2019 recommendations of the European Alliance of Associations for Rheumatology. A working group consisting of rheumatologists from various countries in Latin America identified relevant topics for the treatment of PsA in the region. The methodology team updated the evidence and synthesized the information used to generate the final recommendations. These were then discussed and defined by a panel of 31 rheumatologists from 15 countries. Results Theses guidelines report 15 recommendations addressing therapeutic targets, use of antiinflammatory agents and corticosteroids, treatment with disease-modifying antirheumatic drugs (conventional synthetic, biologic, and targeted synthetic), therapeutic failure, optimization of biologic therapy, nonpharmacological interventions, assessment tools, and follow-up of patients with PsA. Conclusion Here we present a set of recommendations to guide decision making in the treatment of PsA in Latin America, based on the best evidence available, considering resources, medical expertise, and the patient's values and preferences. The successful implementation of these recommendations should be based on clinical practice conditions, healthcare settings in each country, and a tailored evaluation of patients.